Survey of the symptoms and viruses associated with cowpea (Vigna unguiculata (L.)) in the agroecological zones of Kwara State, Nigeria - Aliyu, T.H.; Balogun, O.S.; Kumar, L. (African Journals Online, 2012)
A comprehensive field survey was carried out in 2011 spanning thirty locations within the forest and savannah agroecologies of Kwara State, Nigeria. This was with the objective of having an overview of the prevalence of virus disease symptoms and to specifically identify the viruses infecting cowpea (Vigna unguiculata .L.) in Kwara State. Data were collected on the prevalence of some peculiar virus symptoms on cowpea plants on growing on farms in each location. Symptomatic cowpea leaves were also collected from each location for virus identification in the laboratory. The serological protocol employed for virus detection in the leaf samples was the antigen – coated plate Enzyme linked immunosorbent assay (ACP–ELISA) method. The results of the field survey indicated that the symptoms observed on the cowpea plants were peculiar to those associated with virus disease infection. The symptoms observed were leaf mottling (36.8%), mosaic (24.9%), leaf curl (15.6%), necrotic spots (8.2%) and other symptoms (14.5%). The result of the laboratory assay to detect the viruses present in the leaf samples revealed the presence of four (4) different viruses. The viruses identified were, Cowpea Aphid Borne Mosaic Virus (CABMV), Cowpea Yellow Mosaic Virus (CYMV), Blackeye Cowpea Mosaic Virus (BICMV) and Cowpea Mottle Virus (CPMoV). These viruses were detected infecting the cowpea plants in mixtures of two or three. These results are indicative of the presence of viruses in all the ecological zones of Kwara State where cowpea is cultivated.